2022
DOI: 10.3390/metabo12100886
|View full text |Cite
|
Sign up to set email alerts
|

Low Birth Weight Intensifies Changes in Markers of Hepatocarcinogenesis Induced by Fructose Consumption in Rats

Abstract: Intrauterine growth restriction (IUGR) due to fetal exposure to glucocorticoid excess results in metabolic inflexibility and hepatic steatosis upon nutritional stress during adulthood. We previously demonstrated that rats born to dexamethasone (DEX)-treated mothers developed hepatic steatosis when exposed to 10% fructose solution during adult life. Persistent triacylglyceride (TAG) accumulation in the liver, in turn, is a feature of non-alcoholic fatty liver disease (NAFLD), which serves as a risk factor for n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…This study revealed that exposure to dexamethasone during pregnancy resulted in reduced blood corticosterone levels in both fetal and postnatal male offspring rats. These results were also reported previously by Almeida et al [ 46 ]. Additionally, the serum IGF1 level and the expression of the IGF1 signaling pathway in the liver were significantly downregulated in male offspring exposed to dexamethasone.…”
Section: Discussionsupporting
confidence: 92%
“…This study revealed that exposure to dexamethasone during pregnancy resulted in reduced blood corticosterone levels in both fetal and postnatal male offspring rats. These results were also reported previously by Almeida et al [ 46 ]. Additionally, the serum IGF1 level and the expression of the IGF1 signaling pathway in the liver were significantly downregulated in male offspring exposed to dexamethasone.…”
Section: Discussionsupporting
confidence: 92%
“…Many studies provided details of correlation analysis to reduce the number of features considered in univariable or multivariable modelling [16,17,20,25,27] and to assess for collinearity between variables [18,28] upon multivariable modelling. Of the 12 studies, half used least absolute shrinkage and selection operator (LASSO) techniques [19,[23][24][25][26][27].…”
Section: Statistical Analysis and Model Developmentmentioning
confidence: 99%